2010
DOI: 10.1111/j.1365-2621.2010.02376.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth characteristics of agrowaste‐immobilised lactobacilli in soymilk during refrigerated storage

Abstract: We aimed at evaluating agricultural wastes as solid supports for the immobilisation of lactobacilli in a liquid media, namely soymilk. Lactobacillus acidophilus FTDC 1331, L. acidophilus FTDC 2631, L. acidophilus FTDC 2333, L. acidophilus FTDC 1733 and L. bulgaricus FTCC 0411 were immobilised on solid supports produced from durian (Durio zibethinus), cempedak (Artocarpus champeden) and mangosteen (Garcinia mangostana). The immobilised cells were inoculated into soymilk and stored at 4°C over 168 h. Soymilk ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…We have previously shown that these led to increased proliferation of agrowastes‐immobilized cells in soymilk compared to free cells (Teh et al , 2009), and in the present study, this has led to increased proteolysis. Our previous studies also showed that immobilized cells had better growths at 25°C compared to 4°C and 37°C (Teh et al , 2009, 2010a, b), which was in tandem with the higher degree of proteolytic activity in soymilk at 25°C in the present study.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…We have previously shown that these led to increased proliferation of agrowastes‐immobilized cells in soymilk compared to free cells (Teh et al , 2009), and in the present study, this has led to increased proteolysis. Our previous studies also showed that immobilized cells had better growths at 25°C compared to 4°C and 37°C (Teh et al , 2009, 2010a, b), which was in tandem with the higher degree of proteolytic activity in soymilk at 25°C in the present study.…”
Section: Resultssupporting
confidence: 85%
“…We have previously reported that agrowastes are efficient immobilizers for lactobacilli cells in the fermentation of soymilk. Immobilized cells showed better growth, utilization of substrates and production of short‐chain fatty acids during prolonged fermentation at different temperatures (4°C, 25°C, 36°C) compared to free cells (Teh et al , 2009, 2010a, b). However, the effect of such immobilization on the bioactivity of fermented soymilk remains unknown.…”
Section: Introductionmentioning
confidence: 99%